2021
DOI: 10.1302/0301-620x.103b3.bjj-2020-1421.r1
|View full text |Cite
|
Sign up to set email alerts
|

Does shape and size of the stems affect the stress-shielding around press-fit radial head arthroplasty?

Abstract: Aims It has been hypothesized that proximal radial neck resorption (PRNR) following press-fit radial head arthroplasty (RHA) is due to stress-shielding. We compared two different press-fit stems by means of radiographs to investigate whether the shape and size of the stems are correlated with the degree of PRNR. Methods The radiographs of 52 RHAs were analyzed both at 14 days postoperatively and after two years. A cylindrical stem and a conical stem were implanted in 22 patients (group 1) and 30 patients (grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 32 publications
0
8
1
Order By: Relevance
“…These observations suggest that the aetiology of PRNR may be multifactorial, as has been suggested previously. 7 In our opinion, damage to vascularization in the radial neck during surgery may represent one of these causes.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…These observations suggest that the aetiology of PRNR may be multifactorial, as has been suggested previously. 7 In our opinion, damage to vascularization in the radial neck during surgery may represent one of these causes.…”
Section: Discussionmentioning
confidence: 93%
“…Few studies have been published on PRNR after RHA. 6,7,13 Chanlalit et al 6 radiologically evaluated 26 patients with different types of RHA and found that 65% displayed PRNR after a mean follow-up of 33 months, with no significant differences between stems that were cemented or press-fitted, had a curved or straight stem, or were smooth or rough. Moreover, the authors observed that PRNR started between the first and the 15th month after surgery and did not progress markedly beyond 26 months.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations